High-strength microcrystalline glass and preparation method thereof

By using modified carbon fibers and boron nitride and other raw materials, high-strength microcrystalline glass is prepared, which solves the gap and bubble problems of microcrystalline glass during the composite fiber reinforcement process, achieving both high toughness and strength, suitable for aerospace and optics field.

CN119161107AActive Publication Date: 2024-12-20CHANGSHU JIAHE DISPLAY TECH CO LTD

Patent Information

Application Number
CN202411324143.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-20
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

Existing microcrystalline glasses are prone to gaps and bubbles during the reinforcement of composite fibers, resulting in a decrease in mechanical strength, making it difficult to maintain mechanical strength while improving toughness.

Method used

Using broken glass, titanium dioxide, spodumene, potassium carbonate, lanthanum oxide, barium oxide, zirconia and modified carbon fiber as raw materials, high-strength microcrystalline glass is prepared through smelting, annealing and crystallization steps, using boron nitride and modified Carbon fiber reinforced glass toughness and thermal conductivity.

Benefits of technology

The prepared high-strength microcrystalline glass is widely used in aerospace, optics, and microelectronics fields. It has high toughness, strength, thermal conductivity and heat resistance, reducing the risk of fracture and energy consumption.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to high-strength microcrystalline glass and a preparation method thereof, and belongs to the technical field of composite materials. The high-strength glass ceramic is prepared from cullet, titanium dioxide, spodumene, potassium carbonate, lanthanum oxide, boron nitride, barium oxide, zirconium oxide and modified carbon fibers as raw materials, and the invention further discloses a formula of the raw materials. According to the high-strength glass ceramic, the modified carbon fibers serve as a reinforcing phase, the problem that the glass ceramic has brittleness and is prone to breakage is solved, the modified carbon fibers and a glass ceramic base material are good in phase property, and therefore the prepared glass ceramic is excellent in mechanical performance, the highest impact toughness can reach 3.91 KJ / cm < 3 >, the highest compressive strength can reach 371.28 MPa, and the glass ceramic can be used as a high-strength glass ceramic. The breaking strength can reach 46.93 MPa to the maximum, and in addition, the modified carbon fiber can also improve the thermal stability of the microcrystalline glass and solve the yield influence caused by thermal stress.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials, and in particular, relates to high-strength microcrystalline glass and a preparation method thereof. Background Art

[0002] Glass-ceramics, also known as ceramic glass or crystallized glass, is a type of composite material that originated in the United States and then quickly rose in Japan. my country's research on glass-ceramics began in the 1980s, and after decades of research, the production process has basically matured. Glass-ceramics is a polycrystalline solid obtained by devitrification of glass. It has a beautiful overall appearance and is easy to process. Its microstructure is uniform and dense, without pores, and has a smooth surface. This structure significantly improves the softening temperature, thermal stability, chemical stability, and mechanical strength of glass-ceramics. It has been widely used in many fields such as architecture, aerospace, optics, and electronics.

[0003] Although microcrystalline glass has good mechanical strength, it is still a brittle material due to its structure and is prone to breakage when subjected to strong impact and load. Composite fiber materials such as carbon fiber and basalt fiber are often used in the prior art to enhance the toughness of microcrystalline glass. However, there is still a problem of poor compatibility between fiber materials and microcrystalline glass. During the crystallization and firing process of microcrystalline glass plates made of composite fiber materials, millimeter-level gaps and bubbles may appear underneath. These bubbles and gaps will cause the mechanical strength of the substrate to further decrease. How to improve the toughness of microcrystalline glass without affecting the mechanical strength of the microcrystalline glass itself has become an urgent problem that needs to be solved at this stage. Summary of the invention

[0004] The object of the present invention is to provide high-strength microcrystalline glass and a preparation method thereof, so as to solve the problems mentioned in the above background technology.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] High-strength microcrystalline glass, comprising the following raw materials in parts by weight: 52-59 parts of cullet, 4-6 parts of titanium dioxide, 9-11 parts of spodumene, 13-17 parts of potassium carbonate, 2-2.5 parts of lanthanum oxide, 3-4 parts of boron nitride, 2-3 parts of barium oxide, 1.5-2 parts of zirconium oxide, and 4-5 parts of modified carbon fiber;

[0007] The method for preparing the high-strength microcrystalline glass comprises the following steps:

[0008] Step 1: Weigh each raw material by mass, mix the broken glass, titanium dioxide, spodumene, potassium carbonate, lanthanum oxide, barium oxide and zirconium oxide evenly, place them in a glass kiln, and heat and melt them into glass liquid;

[0009] Step 2: crush the modified carbon fiber, and spray boron nitride and modified carbon fiber powder into the powder through a nitrogen protective gas flow and mix them evenly to obtain a modified carbon fiber glass liquid;

[0010] Step 3: adding the modified carbon fiber glass liquid obtained in the second step into the preheated graphite mold and annealing to obtain the rough glass;

[0011] Step 4: Nucleate and crystallize the crude glass obtained in the third step to obtain high-strength microcrystalline glass.

[0012] Furthermore, in the first step, the temperature condition for heating and melting the molten glass in the glass furnace is 1400-1500° C., and the melting time condition is 4-6 hours.

[0013] Furthermore, in the second step, the particle size specification of the modified carbon fiber powder is 20-40 μm.

[0014] Furthermore, in the third step, the preheating temperature of the graphite mold is 450-550° C., the annealing temperature is 400-500° C., and the annealing time is 3-4 hours.

[0015] Furthermore, in the fourth step, the nucleation temperature of the crude glass is 500-700° C., the nucleation time condition is 3-6 hours, the crystallization temperature is 700-900° C., and the crystallization time condition is 4-8 hours.

[0016] Further, the modified carbon fiber is prepared by the following steps:

[0017] Step 1: Wind the carbon fiber on a glass frame, then place the glass frame wrapped with the carbon fiber in a supercritical extraction reactor, add acetone to the reactor, close the reactor, clean it for 25-40 minutes, and then place it in an oven at 50°C for 12 hours to dry, to obtain surface-treated carbon fiber;

[0018] Step 2: Mix the surface treated carbon fiber and nitric acid solution in a flask, start magnetic stirring, react at a temperature of 40-70°C for 3-4 hours, and after the reaction is completed, vacuum filter, wash the obtained solid with acetone, and heat it in an oven at a temperature of 50°C for 12 hours to obtain surface oxidized carbon fiber;

[0019] Step 3: Mix dodecafluoroheptanol and sodium hydroxide solution in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, and add epichlorohydrin to the three-necked flask with a high-pressure dropping pump under nitrogen protection. After the addition is completed, react at a temperature of 70-90°C for 4-6h. After the reaction is completed, wash with deionized water 3 times, separate the organic layer with a separatory funnel, and rotary evaporate to obtain intermediate 1;

[0020] Step 4: Mix the intermediate 1, 3-aminopropyltriethoxysilane and chloroform in a three-necked flask, install a condenser and a thermometer, start magnetic stirring, and react at a temperature of 50-70°C for 12-15h. After the reaction is completed, rotary evaporation is performed to obtain the intermediate 2;

[0021] Step 5: Mix the surface oxidized carbon fiber, intermediate 2, N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and chloroform in a three-necked flask, install a condenser and a thermometer, turn on the magnetic stirring, react at a temperature of 40-50°C for 18-24h, and after the reaction is completed, vacuum filter, wash the obtained solid with acetone 3 times, and then heat it in an oven at a temperature of 50°C for 12h to obtain modified carbon fiber;

[0022] Furthermore, in step 1, the pressure parameter condition of the supercritical extraction reactor is 8-12 MPa, and the temperature parameter condition is 35-45°C.

[0023] Furthermore, the nitric acid solution used in step 2 is an aqueous nitric acid solution with a molar concentration of 8 mol / L, and the amount ratio of the surface treated carbon fiber to the nitric acid is 3 g:60 mL.

[0024] Furthermore, the sodium hydroxide solution used in step 3 is a sodium hydroxide aqueous solution with a molar concentration of 6 mol / L, and the amount ratio of dodecafluoroheptanol, sodium hydroxide solution and epichlorohydrin used is 0.1 mol:50-80 mL:0.11-0.13 mol.

[0025] Furthermore, the usage ratio of the intermediate 1, 3-aminopropyltriethoxysilane and chloroform used in step 4 is 0.08 mol: 0.09-0.11 mol: 80-120 mL.

[0026] Furthermore, the amount ratio of the surface oxidized carbon fiber, intermediate 2, N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and chloroform used in step 5 is 3g:0.3-0.5g:0.9-1g:2.1-2.4g:60-80mL.

[0027] Beneficial effects of the present invention:

[0028] 1) The present invention uses broken glass, titanium dioxide, spodumene, potassium carbonate, lanthanum oxide, barium oxide, zirconium oxide, boron nitride and modified carbon fiber as raw materials to prepare a high-strength microcrystalline glass; the present invention first mixes broken glass, titanium dioxide, spodumene, potassium carbonate, lanthanum oxide, barium oxide and zirconium oxide to melt into glass liquid, then uses protective nitrogen to disperse modified carbon fiber powder and boron nitride in the glass liquid, and obtains a high-strength microcrystalline glass through annealing, nucleation and crystallization steps; the formula of the present invention recycles broken glass, and titanium dioxide is added to regulate the crystallization process of glass, thereby reducing energy loss, being economical and environmentally friendly, and the formula also adds modified carbon fiber powder with good tensile strength and boron nitride with good thermal conductivity, so that the prepared glass has good toughness, high strength and good thermal conductivity, and can be widely used in the fields of aerospace, optics and microelectronics.

[0029] 2) The present invention uses carbon fiber as a raw material, uses supercritical carbon dioxide to clean the carbon fiber surface slurry to obtain surface-treated carbon fiber, and then uses a nitric acid solution to oxidize the surface-treated carbon fiber to oxidize the hydroxyl group on the carbon fiber surface to a carboxyl group to obtain a surface-oxidized carbon fiber; at the same time, the present invention uses dodecafluoroheptanol as a raw material, and reacts with epichlorohydrin under alkaline conditions with nitrogen protection to undergo a nucleophilic substitution reaction to obtain a surface-epoxidized intermediate 1, and then the epoxy group of the intermediate 1 is subjected to an amidation reaction with the amino group of 3-aminopropyltriethoxysilane to obtain an intermediate 2 containing an organosilicon structure, and finally the amino group of the intermediate 2 is subjected to an amidation reaction with the carboxyl group of the surface-oxidized carbon fiber under the catalysis of an N-hydroxysuccinimide / 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride system to obtain a modified carbon fiber grafted with a long fluorocarbon chain and an organosilicon structure; the carbon fiber is a high-performance The invention discloses a kind of energy fiber material, whose tensile strength is 7-9 times that of steel material and has good chemical stability. The invention first cleans the surface slurry of carbon fiber by supercritical carbon dioxide, and uses acetone as an additive. Acetone, as a polar solvent, can enhance the solubility of supercritical carbon dioxide for polar substances. The interaction between the two can achieve a better cleaning effect, so that the cleaned carbon fiber has better reactivity. The modified carbon fiber contains an organic silicon structure, which can not only repair the surface defects of carbon fiber so that the carbon fiber has better single-filament tensile strength, but also form an effective chemical bond connection at the interface between the modified carbon fiber and silicon dioxide, so that the modified carbon fiber and the microcrystalline glass matrix are more fully combined and the mechanical properties of the interface are enhanced. In addition, the modified carbon fiber also has a large number of carbon-fluorine bonds, which have a large bond energy and are not easily corroded by acids and alkalis. They can also provide better heat resistance and thermal stability when used for microcrystalline glass.

[0030] 3) The high-strength microcrystal preparation process of the present invention is economical and environmentally friendly, the reinforcing phase has good compatibility with the microcrystalline glass substrate, the finished glass has high strength, good toughness, is not prone to breakage, and has good thermal conductivity and heat resistance, and is less affected by yield and fatigue due to thermal stress, and can be widely used in aerospace, optics, and microelectronics fields. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] A modified carbon fiber comprises the following preparation steps:

[0034] Step 1: Wind the carbon fiber on the frame, then place the frame wrapped with the carbon fiber into a supercritical extraction reactor, add acetone into the reactor, then close the reactor, control the pressure parameter to 8MPa, control the temperature parameter to 35°C, wash for 25 minutes, heat and dry at 50°C for 12 hours to obtain surface-treated carbon fiber;

[0035] Step 2: 3 g of surface-treated carbon fiber and 60 mL of 8 mol / L nitric acid aqueous solution were mixed in a container, stirred evenly, and reacted at 40°C for 3 h. After the reaction was completed, vacuum filtered, the obtained solid was washed with acetone, and dried at 50°C for 12 h to obtain surface oxidized carbon fiber;

[0036] Step 3: 0.1 mol of dodecafluoroheptanol and 50 mL of an aqueous sodium hydroxide solution with a molar concentration were mixed in a container, and after stirring evenly, 0.11 mol of epichlorohydrin was added dropwise to the container under nitrogen protection. After the addition was completed, the mixture was reacted at 70° C. for 4 h. After the reaction was completed, the mixture was washed with deionized water for 3 times, and the organic layer was separated by a separatory funnel, and then rotary evaporated to obtain intermediate 1;

[0037] Step 4: 0.08 mol of intermediate 1, 0.09 mol of 3-aminopropyltriethoxysilane and 80 mL of chloroform were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 50-70°C for 12-15 hours. After the reaction was completed, the intermediate 2 was obtained by rotary evaporation;

[0038] Step 5: Mix 3 g of surface oxidized carbon fiber, 0.3 g of intermediate 2, 0.9 g of N-hydroxysuccinimide, 2.1 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 60 mL of chloroform in a container, stir evenly, and react at 40 ° C for 18 h. After the reaction is completed, vacuum filter, wash the obtained solid with acetone 3 times, and then heat and dry it at 50 ° C for 12 h to obtain a modified carbon fiber.

[0039] Example 2

[0040] A modified carbon fiber comprises the following preparation steps:

[0041] Step 1: Wind the carbon fiber on the frame, then place the frame wrapped with the carbon fiber into a supercritical extraction reactor, add acetone into the reactor, then close the reactor, control the pressure parameter to 10MPa, control the temperature parameter to 40°C, wash for 37.5min, and heat and dry at 50°C for 12h to obtain surface-treated carbon fiber;

[0042] Step 2: 3 g of surface-treated carbon fiber and 60 mL of 8 mol / L nitric acid aqueous solution were mixed in a container, stirred evenly, and reacted at 55°C for 3.5 h. After the reaction was completed, vacuum filtration was performed, and the obtained solid was washed with acetone, and then heated at 50°C for 12 h to obtain surface oxidized carbon fiber;

[0043] Step 3: 0.1 mol of dodecafluoroheptanol and 65 mL of a sodium hydroxide aqueous solution with a molar concentration were mixed in a container, and after stirring evenly, 0.12 mol of epichlorohydrin was added dropwise to the container under nitrogen protection. After the addition was completed, the mixture was reacted at 80° C. for 5 h. After the reaction was completed, the mixture was washed with deionized water for 3 times, and the organic layer was separated by a separatory funnel, and then rotary evaporated to obtain intermediate 1;

[0044] Step 4: 0.08 mol of intermediate 1, 0.1 mol of 3-aminopropyltriethoxysilane and 100 mL of chloroform were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 60°C for 13.5 hours. After the reaction was completed, intermediate 2 was obtained by rotary evaporation;

[0045] Step 5: Mix 3 g of surface oxidized carbon fiber, 0.4 g of intermediate 2, 0.95 g of N-hydroxysuccinimide, 2.25 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 70 mL of chloroform in a container, stir evenly, and react at 45 ° C for 21 h. After the reaction is completed, vacuum filter, wash the obtained solid with acetone 3 times, and then heat and dry it at 50 ° C for 12 h to obtain a modified carbon fiber.

[0046] Example 3

[0047] A modified carbon fiber comprises the following preparation steps:

[0048] Step 1: Wind the carbon fiber on the frame, then place the frame wrapped with the carbon fiber into a supercritical extraction reactor, add acetone into the reactor, then close the reactor, control the pressure parameter to 12MPa, control the temperature parameter to 45°C, wash for 40 minutes, heat and dry at 50°C for 12 hours to obtain surface-treated carbon fiber;

[0049] Step 2: 3 g of surface-treated carbon fiber and 60 mL of 8 mol / L nitric acid aqueous solution were mixed in a container, stirred evenly, and reacted at 70°C for 4 h. After the reaction was completed, vacuum filtered, the obtained solid was washed with acetone, and dried at 50°C for 12 h to obtain surface oxidized carbon fiber;

[0050] Step 3: 0.1 mol of dodecafluoroheptanol and 80 mL of an aqueous sodium hydroxide solution with a molar concentration were mixed in a container, and after stirring evenly, 0.13 mol of epichlorohydrin was added dropwise to the container under nitrogen protection. After the addition was completed, the mixture was reacted at 90° C. for 6 h. After the reaction was completed, the mixture was washed with deionized water for 3 times, and the organic layer was separated by a separatory funnel, and then rotary evaporated to obtain intermediate 1;

[0051] Step 4: 0.08 mol of intermediate 1, 0.11 mol of 3-aminopropyltriethoxysilane and 120 mL of chloroform were mixed in a three-necked flask, a condenser and a thermometer were installed, magnetic stirring was turned on, and the reaction was carried out at a temperature of 70°C for 15 hours. After the reaction was completed, intermediate 2 was obtained by rotary evaporation;

[0052] Step 5: Mix 3 g of surface oxidized carbon fiber, 0.5 g of intermediate 2, 1 g of N-hydroxysuccinimide, 2.4 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 80 mL of chloroform in a container, stir evenly, and react at 50 ° C for 24 h. After the reaction is completed, vacuum filter, wash the obtained solid with acetone 3 times, and then heat and dry it at 50 ° C for 12 h to obtain a modified carbon fiber.

[0053] Example 4

[0054] A high-strength microcrystalline glass, comprising the following raw materials in parts by mass: 52 parts of cullet, 4 parts of titanium dioxide, 9 parts of spodumene, 13 parts of potassium carbonate, 2 parts of lanthanum oxide, 3 parts of boron nitride, 2 parts of barium oxide, 1.5 parts of zirconium oxide, and 4 parts of modified carbon fiber obtained in Example 1;

[0055] The method for preparing the high-strength microcrystalline glass comprises the following steps:

[0056] Step 1: Weigh each raw material by mass, mix the broken glass, titanium dioxide, spodumene, potassium carbonate, lanthanum oxide, barium oxide and zirconium oxide evenly, put them into a glass kiln, and heat them at 1400°C for 4 hours to melt them into glass liquid;

[0057] Step 2: The modified carbon fiber obtained in Example 1 is crushed into a powder with a particle size of 20 μm, and the boron nitride and the modified carbon fiber powder are sprayed into the powder through a nitrogen protective gas flow and fully mixed to obtain a modified carbon fiber glass liquid;

[0058] Step 3: Add the modified carbon fiber glass liquid obtained in the second step into a graphite mold preheated at 450°C, cool to 400°C, anneal and keep warm for 3 hours to obtain a rough glass;

[0059] Step 4: The crude glass obtained in the third step is kept at 500°C for 3 hours for nucleation and at 700°C for 4 hours for crystallization to obtain a high-strength microcrystalline glass.

[0060] Example 5

[0061] A high-strength microcrystalline glass, comprising the following raw materials in parts by mass: 52 parts of cullet, 6 parts of titanium dioxide, 9 parts of spodumene, 13 parts of potassium carbonate, 2.5 parts of lanthanum oxide, 3 parts of boron nitride, 3 parts of barium oxide, 2 parts of zirconium oxide, and 4 parts of modified carbon fiber obtained in Example 2;

[0062] The method for preparing the high-strength microcrystalline glass comprises the following steps:

[0063] Step 1: Weigh each raw material by mass, mix the broken glass, titanium dioxide, spodumene, potassium carbonate, lanthanum oxide, barium oxide and zirconium oxide evenly, put them into a glass kiln, and heat them at 1450°C for 5 hours to melt them into glass liquid;

[0064] Step 2: The modified carbon fiber obtained in Example 2 is crushed into a powder with a particle size of 30 μm, and the boron nitride and the modified carbon fiber powder are sprayed into the powder through a nitrogen protective gas flow and fully mixed to obtain a modified carbon fiber glass liquid;

[0065] Step 3: Add the modified carbon fiber glass liquid obtained in the second step into a graphite mold preheated at 500°C, cool to 450°C, anneal and keep warm for 3.5 hours to obtain a rough glass;

[0066] Step 4: The crude glass obtained in the third step is kept at 600°C for 4.5 hours for nucleation and at 800°C for 6 hours for crystallization to obtain a high-strength microcrystalline glass.

[0067] Example 6

[0068] A high-strength microcrystalline glass, comprising the following raw materials in parts by mass: 59 parts of cullet, 4 parts of titanium dioxide, 11 parts of spodumene, 17 parts of potassium carbonate, 2 parts of lanthanum oxide, 4 parts of boron nitride, 2 parts of barium oxide, 1.5 parts of zirconium oxide, and 5 parts of modified carbon fiber obtained in Example 3;

[0069] The method for preparing the high-strength microcrystalline glass comprises the following steps:

[0070] Step 1: Weigh each raw material by mass, mix the broken glass, titanium dioxide, spodumene, potassium carbonate, lanthanum oxide, barium oxide and zirconium oxide evenly, put them into a glass kiln, and heat them at 1500°C for 6 hours to melt them into glass liquid;

[0071] Step 2: The modified carbon fiber obtained in Example 3 is crushed into a powder with a particle size of 40 μm, and the boron nitride and modified carbon fiber powder are sprayed into the powder through a nitrogen protective gas flow and fully mixed to obtain a modified carbon fiber glass liquid;

[0072] Step 3: Add the modified carbon fiber glass liquid obtained in the second step into a graphite mold preheated at 550°C, cool to 500°C, anneal and keep warm for 4 hours to obtain a rough glass;

[0073] Step 4: The crude glass obtained in the third step is kept at 700°C for 6 hours for nucleation and at 900°C for 8 hours for crystallization to obtain a high-strength microcrystalline glass.

[0074] Comparative Example 1

[0075] The raw material "modified carbon fiber obtained in Example 3" used in Example 6 was replaced with ordinary carbon fiber, and the other conditions and steps remained unchanged.

[0076] Comparative Example 2

[0077] This comparative example is the microcrystalline glass sold by Dongguan Mingda Glass Co., Ltd.

[0078] The mechanical properties of the high-strength glass-ceramics in Examples 4-6 and Comparative Example 1 and the glass-ceramics sold by Dongguan Mingda Glass Co., Ltd. in Comparative Example 2 were tested together. The test results are shown in Table 1:

[0079] Table 1

[0080] project Flexural strength(MPa) Compressive strength(MPa) <![CDATA[Impact toughness (KJ / cm 3 )]]> Example 4 44.81 357.39 3.49 Example 5 46.93 371.28 3.91 Example 6 41.69 351.19 3.26 Comparative Example 1 26.95 327.29 2.34 Comparative Example 2 32.45 303.24 2.67

[0081] It can be seen from Table 1 that the high-strength microcrystalline glass of Examples 4-6 are superior to the commercially available microcrystalline glass in terms of compressive strength, flexural strength and impact toughness. Although the high-strength microcrystalline glass of Comparative Example 1 is still better than the commercially available microcrystalline glass in compressive strength, its flexural strength and impact toughness are not good. This may be because the carbon fiber powder and the microcrystalline glass matrix have poor compatibility, resulting in bubbles or gaps and causing the mechanical properties to deteriorate. Based on Table 1, it can be concluded that the modified carbon fiber of the present invention is used for microcrystalline glass to effectively improve the mechanical properties of the microcrystalline glass. The microcrystalline glass of the present invention has excellent mechanical properties and is not prone to breakage. It can be widely used in aerospace, optics, and microelectronics fields.

[0082] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. High-strength glass-ceramics, characterized in that: The raw materials include the following parts by weight: 52-59 parts of cullet, 4-6 parts of titanium dioxide, 9-11 parts of spodumene, 13-17 parts of potassium carbonate, 2-2.5 parts of lanthanum oxide, 3-4 parts of boron nitride, 2-3 parts of barium oxide, 1.5-2 parts of zirconium oxide, and 4-5 parts of modified carbon fiber; Wherein, the modified carbon fiber is made by the following steps: Step 1: Wind the carbon fiber on a frame, then place the frame wrapped with the carbon fiber into a supercritical extraction reactor, add acetone into the reactor, then close the reactor, and wash for 25-40 minutes to obtain surface-treated carbon fiber; Step 2: Mix the surface treated carbon fiber and nitric acid solution in a container, stir evenly, and react at a temperature of 40-70° C. for 3-4 hours to obtain surface oxidized carbon fiber; Step 3: dodecafluoroheptanol and sodium hydroxide solution are mixed in a container, stirred evenly, and then epichlorohydrin is added dropwise to the container under nitrogen protection. After the addition is complete, the mixture is reacted at 70-90° C. for 4-6 hours to obtain intermediate 1; Step 4: Mix the intermediate 1, 3-aminopropyltriethoxysilane and chloroform in a container, stir evenly, and react at a temperature of 50-70° C. for 12-15 hours to obtain the intermediate 2; Step 5: Mix the surface oxidized carbon fiber, intermediate 2, N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and chloroform in a container, stir evenly, and react at a temperature of 45-50° C. for 18-24 hours to obtain modified carbon fiber.

2. The high-strength microcrystalline glass according to claim 1, characterized in that: In step 1, the pressure parameter condition of the supercritical extraction reactor is 8-12 MPa, and the temperature parameter condition is 35-45°C.

3. The high-strength microcrystalline glass according to claim 1, characterized in that: The nitric acid solution used in step 2 is an aqueous nitric acid solution with a molar concentration of 8 mol / L, and the amount ratio of the surface treated carbon fiber to the nitric acid is 3 g:60 mL.

4. The high-strength microcrystalline glass according to claim 1, characterized in that: The sodium hydroxide solution used in step 3 is a sodium hydroxide aqueous solution with a molar concentration of 6 mol / L, and the amount ratio of the used dodecafluoroheptanol, sodium hydroxide solution and epichlorohydrin is 0.1 mol:50-80 mL:0.11-0.13 mol.

5. The high-strength glass-ceramics according to claim 1, characterized in that: The amount ratio of the intermediate 1, 3-aminopropyltriethoxysilane and chloroform used in step 4 is 0.08 mol: 0.09-0.11 mol: 80-120 mL.

6. The high-strength glass-ceramics according to claim 1, characterized in that: The amount ratio of the surface oxidized carbon fiber, intermediate 2, N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and chloroform used in step 5 is 3g:0.3-0.5g:0.9-1g:2.1-2.4g:60-80mL.

7. A method for preparing high-strength microcrystalline glass, characterized in that: The following steps are involved: Step 1: Weigh each raw material by mass, mix the broken glass, titanium dioxide, spodumene, potassium carbonate, lanthanum oxide, barium oxide and zirconium oxide evenly, place them in a glass kiln, and heat and melt them into glass liquid; Step 2: crush the modified carbon fiber, and spray boron nitride and modified carbon fiber powder into the powder through a nitrogen protective gas flow and mix them evenly to obtain a modified carbon fiber glass liquid; Step 3: adding the modified carbon fiber glass liquid obtained in the second step into the preheated graphite mold and annealing to obtain the rough glass; Step 4: Nucleate and crystallize the crude glass obtained in the third step to obtain high-strength microcrystalline glass.

8. The method for preparing high-strength glass-ceramics according to claim 7, characterized in that: In the first step, the temperature condition of heating and melting the glass liquid in the glass kiln is 1400-1500° C., and the melting time condition is 4-6 hours. In the second step, the particle size specification of the modified carbon fiber powder is 20-40 μm.

9. The method for preparing high-strength glass-ceramics according to claim 7, characterized in that: In the third step, the preheating temperature of the graphite mold is 450-550°C, the annealing temperature is 400-500°C, and the annealing time is 3-4h.

10. The method for preparing high-strength glass-ceramics according to claim 7, characterized in that: In the fourth step, the nucleation temperature of the crude glass is 500-700° C., the nucleation time condition is 3-6 hours, the crystallization temperature is 700-900° C., and the crystallization time condition is 4-8 hours.

Citation Information

Patent Citations

  • Glass ceramic bowl with good strength and preparation process thereof

    CN104150774A

  • Carbon fiber baryta feldspar glass ceramics multiphase material and preparation method thereof

    CN106630639A

  • Carbon fiber phlogopite glass ceramics multiphase material and preparation method thereof

    CN106630657A

  • Glass ceramic for commercial induction cooker panels and preparation method thereof

    CN108409141A

  • Acid / alkali resistant flux for low-temperature corrosion-resistant pigment for ceramic wine bottle

    CN110128854A

Cited By

  • High-strength impact-resistant glass product and preparation method thereof

    CN122079493A

  • A high-strength impact-resistant glass product and its preparation method

    CN122079493B